APPLICATION OF RECEPTION THEORY AND LITERARY ECOLOGY THROUGH READING SHORT STORIES ON ENVIRONMENTAL THEMES - Iswan Afandi (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
The purpose of this study is to describe students’ perceptions in the short story entitled Bumi Tak Seindah Dulu by determining: 1) theme; 2) characterizations; 3) the view of the main character (Mother) on the environment in which they live; 4) the relationship between the main character (Mother) and the environment in which she lives; 5) how important the environment is in human life. This type of research is descriptive and qualitative. The theory used is literary reception theory and eco-critical theory. The research instruments are short story text and questionnaire. Data collection techniques used in this research are questionnaire, reading, and note-taking techniques. The results of the study, namely: (1) the theme in the short story entitled Bumi Tak Seindah Dulu, namely environmental damage was perceived by 8 (28%) students and varied themes amounted to 20 (72%) students; (2) the characterizations, which are played by the character Ibu who has caring attitude towards the condition of the teak forest which is perceived by 9 (11.25%) students and varied perceptions of 19 (67%) students; 3) the view of the main character (Mother) on the environment in which they live, namely the character perceives a change in the environment is perceived by 7 (25%), forest care figures are perceived by 9 (33%) students, and varied perceptions are 12 (42%) students ; 4) the relationship between the main character (Mother) and the natural environment, namely the character has a relationship with the natural world is perceived by 11 (40%) students and varied perceptions of 17 (60%) students; and 5) about the importance of the environment in life, namely students said it was important that we continue to preserve the environment, which was perceived by 11 (39%) students and varied perceptions of 17 (60%) students.